Study of the Performance of Batch Reactive Distillation Column - K. Haweel, Cecilia; M.A. Hamza, Taha (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Batch reactive distillation was studied in packed bed column. Esterification of methanol with acetic acid to produce methyl acetate and water with homogenous sulfuric acid as a catalyst was considered. This system was chosen because the reaction is reversible and the boiling point of reactant and products are different. The reaction was carried out with and without distillation column and shows that the reactive distillation is more efficient from the conventional process (reactor and then separation). The conversion of acetic acid and concentration of methyl acetate increase by (30.43% and 75.14%) respectively at the best condition (reflux ratio 2, feed mole ratio 2 and batch time 90 minute). The influence of various parameters, such as batch time, reflux ratio, and feed mole ratio (methanol to acetic acid) on the performance of the batch reactive distillation column was studied, through the effect of the concentration of product and conversion of reactant. The results obtained for the non-ideal packed bed reactive batch distillation column show that the conversion of acetic acid is 90% at the best condition reflux ratio 2, feed mole ratio 2, and batch time 90 minute